Pemanfaatan Aplikasi Gudang Tadi Untuk Meningkatkan Nilai Jual Hasil Panen Petani - Ertina Sabarita Barus; Diana Alemin Barus (Jurnal Ilmu Komputer dan Sistem Informasi (JIKOMSI), 2023)
The Gudang Tani application is an Android-based application developed using the Android Studio tool which can be used in apk format and can be used for all smartphone platforms. The Gudang Tani application provides menus that can be used for buying and selling transactions, each of these menus is very easy to use. There is also a menu of photos of the products being sold, but this application is not equipped with payments through the application, payments must still be made directly between the seller and the buyer. This application has been implemented for farmers in Singa Village, Tiga Panah, Tanah Karo. Some farmer groups have used it, but there are some who cannot use it because they are still constrained by smartphone devices and farmers are not used to using it.